Rare Earth Elements Recovery from Primary and Secondary Resources Using Flotation: A Systematic Review - Pongsiri Julapong; Apisit Numprasanthai; Ladda Tangwattananukul; Onchanok Juntarasakul; Palot Srichonphaisarn; Kosei Aikawa; Ilhwan Park; Mayumi Ito; Carlito Baltazar Tabelin; Theerayut Phengsaart (Applied Sciences, 2023)
Rare earth minerals (REMs) contain rare earth elements (REEs) that are important in modern technologies due to their unique magnetic, phosphorescent, and catalytic properties. However, REMs are not only non-renewable resources but also non-uniformly distributed on the Earth’s crust, so the processing of REE-bearing secondary resources via recycling is one potential route to ensure the long-term sustainability of REE supply. Flotation—a method that separates materials based on differences in their surface wettability—is a process applied for both mineral processing and recycling of REEs, especially when the particles are fine and/or a high-purity product is required. In this review, studies about rare earth flotation from 2012 to 2021 were systematically reviewed using the PRISMA guideline. It was found that most REM flotation research works focused on finding better collectors and depressants while, for recycling, studies on advanced flotation techniques like froth flotation, ion flotation, solvent sublation, electroflotation, and adsorbing colloid flotation with an emphasis on the recovery of dissolved REEs from aqueous solutions dominated.